Narzędzia controllingu strategicznego w przedsiębiorstwie - analiza porównawcza - Sierpińska, Maria; Dróżdż, Michał (Tools of strategic controlling in enterprise - comparative analysis, 2006)
This paper presents the idea and structure of basic tools of strategic controlling such as Tableau de Bord, Balanced Scorecard, Skandia Navigator. They are all widely used in the companies for implementing the strategy and its accomplishment through operational activity. Such instruments can be compared to steering panel or “a house” and are aimed at equable approach to all fields of company management. They support taking managerial decisions with respect to a long time horizon and at the same time avoid financial results from shading other fields of the company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 103-115